Assessing the utility of trace and rare earth elements as biosignatures in microbial iron oxyhydroxides - Heim, Christine; Simon, Klaus; Ionescu, Danny; Reimer, Andreas; De Beer, Dirk; Quéric, Nadia-Valérie; Reitner, Joachim; Thiel, Volker (Frontiers in Earth Science, 2015)
Microbial iron oxyhydroxides are common deposits in natural waters, recent sediments, and mine drainage systems. Along with these minerals, trace and rare earth elements (TREE) are being accumulated within the mineralizing microbial mats. TREE patterns are widely used to characterize minerals and rocks, and to elucidate their evolution and origin. However, whether and which characteristic TREE signatures distinguish between a biological and an abiological origin of iron minerals is still not well-understood. Here we report on long-term flow reactor studies performed in the Tunnel of Äspö (Äspö Hard Rock Laboratory, Sweden). The development of microbial mats dominated by iron-oxidizing bacteria (FeOB), namely Mariprofundus sp. and Gallionella sp were investigated. The feeder fluids of the flow reactors were tapped at 183 and 290 m below sea-level from two brackish, but chemically different aquifers within the surrounding, ~1.8 Ga old, granodioritic rocks. The experiments investigated the accumulation and fractionation of TREE under controlled conditions of the subsurface continental biosphere, and enabled us to assess potential biosignatures evolving within the microbial iron oxyhydroxides. After 2 and 9 months, concentrations of Be, Y, Zn, Zr, Hf, W, Th, Pb, and U in the microbial mats were 103- to 105-fold higher than in the feeder fluids whereas the rare earth elements and Y (REE+Y) contents were 104- and 106-fold enriched. Except for a hydrothermally induced Eu anomaly, the normalized REE+Y patterns of the microbial iron oxyhydroxides were very similar to published REE+Y distributions of Archaean Banded Iron Formations (BIFs). The microbial iron oxyhydroxides from the flow reactors were compared to iron oxyhydroxides that were artificially precipitated from the same feeder fluid. Remarkably, these abiotic and inorganic iron oxyhydroxides show the same REE+Y distribution patterns. Our results indicate that the REE+Y mirror closely the water chemistry, but they do not allow to distinguish microbially mediated from inorganic iron precipitates. Likewise, all TREE studied showed an overall similar fractionation behavior in biogenic, abiotic, and inorganic iron oxyhydroxides. Exceptions are Ni and Tl, which were only accumulated in the microbial iron oxyhydroxides and may point to a potential utility of these elements as microbial biosignatures.